Defining the gap between electrographic seizure burden, clinical expression and staff recognition of neonatal seizures. Issue 3 (11th July 2007) - Murray, D M; Boylan, G B; Ali, I; Ryan, C A; Murphy, B P; Connolly, S
Abstract : Background: Neonatal seizures are often subclinical, making accurate diagnosis difficult. Objective: To describe the clinical manifestations of electrographic seizures recorded on continuous video-EEG, and to compare this description with the recognition of clinical seizures by experienced neonatal staff. Methods: Term infants, at risk of seizures, were monitored by continuous 12-channel video-EEG from <6 hours of birth for up to 72 hours. All clinical seizures were recorded by experienced neonatal staff on individual seizure charts. Video-EEG recordings were subsequently analysed. The number, duration and clinical expression of electrographic seizures were calculated (in seconds), and compared with the seizures clinically suspected by the neonatal staff. Results: Of 51 infants enrolled, nine had electrographic seizures. A further three had clinically suspected seizures, without associated electrographic abnormality. Of the total 526 electrographic seizures, 179 (34%) had clinical manifestations evident on the simultaneous video recording. The clinical seizure activity corresponded to 18.8% of the total electrographic seizure burden. Overdiagnosis also occurred frequently. Of the 177 clinically suspected seizure episodes documented by staff, 48 (27%) had corresponding electrographic evidence of seizure activity Thus, only 9% (48/526) of electrographic seizures were accompanied by clinical manifestations, which were identified and documented by neonatal staff. Conclusion: Only one-third of neonatal EEG seizures displays clinical signs on simultaneous video recordings. Moreover, two-thirds of these clinical manifestations are unrecognised, or misinterpreted by experienced neonatal staff. In the recognition and management of neonatal seizures clinical diagnosis alone is not enough.